Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pegawai Pada BPS OKU Selatan - Purwanto, Purwanto; Dewi Lubis, Desy Irana; Bahri, Syamsul (Jurnal Wira Ekonomi Mikroskil, 2025)
This study aims to analyze the effect of service quality on employee satisfaction at the BPS Office of Ogan Komering Ulu Selatan Regency. The research method used is a quantitative approach with data collection techniques using a Likert scale-based questionnaire. The sample of this study involved all employees in the office, which was 19 people. The results of the simple linear regression test showed that service quality has a positive and significant effect on employee satisfaction with a regression coefficient of 0.534 and a significance value of 0.002. Validity and reliability tests showed that the research instrument was valid and consistent, with a Cronbach's Alpha value of 0.871 for service quality and 0.887 for employee satisfaction. The analysis of the coefficient of determination (R²) showed that 44.4% of the variation in employee satisfaction was explained by service quality, while 55.6% was influenced by other factors. This study emphasizes the importance of improving service quality in order to increase employee satisfaction and create a productive work environment